Analisis Pendapatan Usaha Ayam Broiler pada Pola dan Skala Yang Berbeda di Peternakan Rakyat Kabupaten Lumajang - Gilang Nursandhi; Hariadi Subagja; Ujang Suryadi (Jurnal Ilmiah Inovasi, 2018)
This research aims to analyze the difference in the level of revenues savor independent patterns and patterns of partnership at different scales, analyze business patterns and scale venture capable of producing the most income levels are high, analyze the relationship between the pattern and scale of effort against the income level, as well as to analyze the influence of factors of production costs against revenue level savor in Lumajang. Research conducted from 1 July until 31 September 2017 using data at one time production period. Sampling determined deliberately by grouping the respondents based on a combination of the pattern of independent business and partnerships, as well as household business scale, small, and medium. The population that used as many as 60 breeders consisting of 10 samples in each group of a combination of patterns and business scale. Data analysis is an analysis of income and multiple linear regression analysis. Bound variables in this study are the level of revenues savor (Y), with free variables that comprise the cost of day-old chick (X1), feed (X2), vaccines, medications, vitamins, and disinfectants (X3), laborer (X4), preparation cost of enclosure and fuel (X5), electricity (X6), depreciation cost of enclosure and equipment (X7), and the pattern of effort selected breeders (D) to run his business. The results of the analysis showed that the level of income breeders partnership is higher than a standalone pattern breeder (3.169 rupiahs > 2.801 rupiahs), whereas small-scale dairy farmers income levels greater than large-scale ranchers and scale house appliances (3.926 rupiahs > 2.564 rupiahs > 2.466 rupiahs). Combinations of patterns of partnership with small-scale yielding the highest income levels compared to the pattern and scale of other businesses. Multiple linear regression analysis results on F test shows that that simultaneously throughout the free variables (X1, X2, X3, X4, X5, X6, X7, and D) effect significantly to the variable (Y). Results on t-test showed that partially variables X1, X2, X3, X4, X7 and influential significantly to variable Y, whereas the variable X5, X6, and D do not affect significantly to the variable Y.Keywords : Income level, Business pattern, and Business scale.